A qualitative analysis of the utility of a competency framework for mentor training. Issue 5 (20th October 2021) - Spiekermann, Lara; Lawrence, Edith; Lyons, Michael; Deutsch, Nancy
ABSTRACT: This study takes a qualitative approach to determining the potential usefulness of a competency framework for mentor training. Participants were 37 college women mentoring middle school girls as part of a school-based mentoring program. Mentors were trained using a competency model designed to help them navigate the nuances and challenges of forming a relationship with an unknown youth. As the first step in empirically evaluating the effectiveness of this approach, this study examines if and how mentors made use of this training in their relationships with their mentees. Findings suggest that mentors applied the competency approach in order to develop stronger relationships and overcome mentoring challenges.